The impact of energy and air emissions in a changing economic structure: Input-output approach - Kobayashi, Kiyoshi; Trinh, Bui; Trung, Vu Dien (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 5E, 2011)
Abstract. Carbon dioxide (CO 2 ) emissions are considered as one of the main sources of climate change. The problem recently arises when we want to identify which are the most caused to CO 2 emission or even which are the most environmentally harmful sectors. This paper presents an attempt for trying to estimate air emission when changing economic structure. The methodology used in the study is based on Miyazawa’s concept of the inter-relational income multiplier, it was designed to analyse the structure of income distribution by final demands in the standard Leontief’s system.   Keywords: Vietnam, input-output analysis, CO 2 emission, economic structure.